Repetition as a means of emotional expression in french poetry used in teaching philology students - Bondaruk, Liudmyla (International University of Applied Sciences in Lomza, 2025)
The article deals with the phenomenon of repetition as a method of teaching French to philology students and as a means of expressing emotional and evaluative attitudes towards speech-related problems in intercultural communication. It is noted that “repetition” is a multivalent concept. It is the object of study in various scientific fields such as psychology, cultural studies, philology, and folklore. Repetition is used in various speech styles, registers, and text genres, therefore it is necessary to clearly distinguish its functional purpose. The ability of philology students to identify the functions of repetition in different text genres, its lexical and semantic features, emotional and evaluative impact on the recipient of information will contribute to the adequate perception of speech and the formation of their constructions in the process of communication. However, it is important to consider the difference between repetition and imitation, tautology and linguistic redundancy, for instance, the excessive use of certain linguistic units, or vice versa, to narrow the message.
Keywords: a phenomenon of repetition; text coherence; teaching method; means of dominant expression; emotional and evaluative speech; imitation; functional purpose